Prinsip musyawarah dalam Al-qur’an: Kajian tafsir maqasidi terhadap ayat-ayat syura - vidhania, Aiska rahma (Maliki Interdisciplinary Journal, 2026)
Deliberation (shura) is one of the important principles in Islam that functions as a means of collective decision-making. This principle not only has social value but also reflects the objectives of Islamic law in line with the concept of maqāṣid al-sharī‘ah. This study aims to examine the concept of deliberation in the Qur’an through a maqāṣidī interpretation approach. The method used in this research is qualitative with a library research approach, using sources from the Qur’an, classical and contemporary tafsir literature, and other relevant references related to the concept of deliberation. This study aims to examine the concept of deliberation (musyawarah) in the Qur’an through a maqāṣidī tafsir approach. The method employed is qualitative, using a library research approach based on the Qur’an, classical and contemporary tafsir works, and other relevant literature on the topic of deliberation. The findings indicate that the concept of musyawarah is reflected in several Qur’anic verses, including QS. Al-Syura (42): 38, QS. Al-Baqarah (2): 233, and QS. Ali Imran (3): 159. These verses emphasize that deliberation is a characteristic of a faithful community and serves as a means to resolve various issues wisely. From the perspective of maqāṣid al-sharī‘ah, deliberation plays a significant role in achieving public welfare (maṣlaḥah), maintaining unity, and preventing authoritarian decision-making. Therefore, musyawarah should not merely be understood as a discussion mechanism, but also as an ethical and social principle aimed at fostering justice, togetherness, and societal well-being.